Uncertainty estimates for atmospheric neutrino fluxes - Barr, G; Gaisser, T; Stanev, T (Universidad Nacional Autonoma de Mexico, 2007)
Starting from a survey of experimental measurements, we assign uncertainties to the two most critical inputs to the calculation of fluxes of unoscillated atmospheric neutrinos, the hadron production and the primary cosmic ray fluxes. We then propagate these uncertainties through the entire flux calculation to arrive at estimates of the uncertainties in the fluxes of neutrinos and of various ratios of neutrino fluxes. We find that there is indeed a significant cancellation of flux uncertainties when these ratios are made. The uncertainties as a function of neutrino energy will be presented.